A motivational interview promotes retention of blood donors with high internal motivation - France, Christopher R. (Transfusion, 2017)
BACKGROUND: Based on the hypothesis that self-determined motivation is associated with an increased likelihood of future behavior, the present study examined the ability of a motivational interview to promote internal motivation for giving and future donation attempts. STUDY DESIGN AND METHODS: A sample of 484 recent whole blood and double red cell donors (62.4% female; mean age = 30.2, SD = 11.8 years) were randomly assigned to either a telephone-delivered motivational interview or a control call approximately six weeks after donating. Several weeks before the call and again one week after the call participants completed the Blood Donor Identity Survey, a multidimensional measure of donor motivation, to derive indices of amotivation, external motivation, and internal motivation to give blood. Repeat donation attempts were tracked using blood center records. RESULTS: Relative to controls, participants in the motivational interview group showed a shift toward more self-determined motivation as indicated by significant decreases in amotivation (p=0.01) and significant increases in external (p=0.009) and internal motivation (p=0.002). Further, those with initially high levels of autonomous motivation were more likely to make a donation attempt in the subsequent year if they completed the motivational interview (71.1%) versus the control call (55.1%). CONCLUSION: Motivational interviewing is a potentially useful strategy to enhance retention of existing blood donors, particularly among those who express a greater sense of internal motivation for giving.